Sharia Insurance Controversy: Fatwa Review and Its Development - Mahmudin, Mahmudin; Nafi, Muhammad; Masuwd, Mowafg (Waralaba : Journal Of Economics and Business, 2025)
Sharia insurance is a solution to the legal dilemma of conventional insurance which is considered to contain elements of gharar and usury. This study examines the concept, legal basis, and criticism of sharia insurance using library research methods. Sharia insurance is based on the principle of mutual assistance (ta'awun) and refers to the fatwa of the National Sharia Council-Indonesian Ulema Council (DSN-MUI). Several relevant fatwas include the provisions of contracts in sharia insurance, such as mudharabah musytarakah, wakalah bil ujrah, and tabarru'. However, sharia insurance still attracts criticism, especially regarding the use of multi-contracts which is considered problematic by some scholars. In addition, there are differences between theoretical concepts and practices in the field, which sometimes deviate from sharia provisions. Nevertheless, sharia insurance continues to develop as an alternative financial protection that is considered in accordance with Islamic values. This study concludes that sharia insurance is acceptable as long as it adheres to sharia principles and DSN-MUI fatwas.